Money or Joy: The Choice of Educational Type - Annette Alstadsæter; Anne-Sofie Kolm; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2005)
This paper examines the effect of taxes on the individuals' choices of educational direction, and thus on the economy.s skill composition. A proportional labour tax induces too many workers with high innate ability to choose an educational type associated with high consumption value and low effort. This increases the skill mismatch and aggregate unemployment in the economy. The government can correct for this distortion by use of differentiated tuition fees or tax rates.
hdl:10398/7562
Keywords: H21; H24; J64; J68; 330; Unemployment; matching; education; optimal taxation; tuition fees